(untitled) (International Journal of Studies in Nursing, 2018)
Aims: The risk of mental illness and mental health problems is known to increase with aging, there is a continuing need for research and information about the daily life and care needs of elderly people with mental illness. The aim of this study was to examine the real-life experience of elderly outpatients with mental illnesses in Taiwan communities through in-depth interviews. Methods: A qualitative study involving semi-structured interviews of mentally ill elderly patients was conducted in 15 participants (3 men and 12 women, mean age = 74.67 years, SD = 10.04 years). Results: The willpower to survive and cope with aging and mental health problems was identified as the core category of the life experiences in the older adults in this study. The struggle with the stress of aging and mental health problems was categorized in life-experience terms as ‘bear the bitterness of life,’ ‘adhere to psychiatric treatment and use resources to cope with life’s stress,’ ‘maintain the willpower to survive’. Results of this study shown that although elderly patients in community have had many stressful life experiences and problems with mental illness, they will continue to show strength to coping with the problems of aging and mental illnesses. Conclusions: The elderly mental illness patients could coping with their problems, and maintain an active lifestyle, accept the reality and arrange life, and connect with the community. Therefore, health professionals should help elderly people find new strategies to maintain their mental health and to function in their communities.